Introduction to definiteness in Ayoreo (Zamucoan) - Durante, Santiago (International Journal of Linguistics and Indigenous Culture, 2026)
Ayoreo, a Zamucoan language of the Gran Chaco, lacks a formal word class for articles, presenting a significant challenge for understanding how universal functional domains of reference are realized in languages with limited descriptions. This research addresses a notable lacuna in the literature regarding a systematic analysis of the grammatical encoding of definiteness in Ayoreo. The primary objective is to characterize the diverse morphosyntactic and discursive mechanisms—including nominal suffixes, possessive prefixes, and demonstratives—that manage identifiability, familiarity, and uniqueness. Employing a mixed onomasiological and semasiological approach, the study analyzes a first-hand corpus collected between 2011 and 2022, supplemented by secondary sources and controlled elicitation. Previous studies reveal a specialized triple nominal marking system: the "full form" serves as the primary vehicle for definite reference, while the "indeterminate form" marks referential but non-specific entities. Additionally, a complex three-degree demonstrative system and possessive prefixes provide essential situational, anaphoric, and associative anchoring. Semantic mapping confirms that proper names and personal pronouns inherently encode uniqueness and familiarity. The study shows that although Ayoreo lacks independent articles, its robust suffixal and pronominal strategies satisfy cross-linguistic criteria for article-like functions. These results contribute essential data to the description of Chaco languages and facilitate broader typological comparisons of referential systems, suggesting that definiteness can be effectively realized through fusional morphology rather than independent word classes.